BANDWIDTH ENHANCEMENT IN DOHERTY POWER AMPLIFIERS: A COMPARISON OF CONVENTIONAL AND INVERTED ARCHITECTURES - Abdulaziz, Abdulrazaq; Adamu, A. A.; Yaro, A. S.; Jibrin, F. A.; Babani, S.; Dankulu, M. H. (FUDMA JOURNAL OF SCIENCES, 2025)
Conventional Doherty power amplifiers (DPAs) face bandwidth issues due to poor impedance matching and input phase design. This paper explores ways to enhance DPA performance in frequency response. The study focuses on optimizing output matching network parameters and the input phase slope between main and auxiliary amplifiers to improve bandwidth efficiency, especially for mobile wireless applications.We calculate the voltage standing wave ratio (VSWR) for each DPA amplification stage at different power levels using MATLAB. We examine conventional and inverted DPA configurations at 2.5 GHz within the 2 GHz to 3 GHz range, utilizing an NXP GaN-based FET transistor model. The two-stage architectures include main amplifiers in Class B and auxiliary in Class C modes, analyzed at peak and back-off levels. Our results indicate that the inverted Doherty amplifier achieves a 40% fractional bandwidth compared to the 8% of the conventional DPA at a VSWR of 1.2, showing better performance due to greater parameter flexibility. These findings are significant for improving RF efficiency in 5G base stations and future wireless networks.
Keywords: Doherty Power Amplifier; Voltage standing wave ratio; Quarter-wave transmission line; Fractional bandwidth